REGULATIONS AND CONCEPTS OF TRADE LEGAL FORM IN THE COUNTRIES OF BRUNEI DARUSSALAM AND INDONESIA - Zulfahmi Harahap; Rico Nur Ilham; Sardi; Henry Aspan (CV. RADJA PUBLIKA, 2024)
This research aims to determine the legal regulations and concepts of trade law in Brunei Darussalam and Indonesia as regulated in the Laws of Brunei, Chapter 106 Contracts. There are 5 points that can be studied from the regulations in these 2 countries, namely: Legal Entity Status, Partnership Establishment, Partnership Organs, Responsibilities and Partnership Dissolution. This is a reference for updating Partnership regulations in Indonesia in the future by referring to Brunei Darussalam state regulations. This research is normative legal research, namely research that prioritizes library research to obtain secondary data. The approach used in this research is a statutory approach.